Superbia Genueńczyków w połowie XIV wieku w oczach bizantyńskich i weneckich historyków i kronikarzy - Karpow, Siergiej Pawłowicz (Przegląd Nauk Historycznych, 2017)
The article treats the approach of the Byzantine and Italian historians and chroniclers of the 14th–17th centuries to the problem of claims of the Republic of Genoa to establish its monopoly in trade and navigation in the Black Sea area. It seemed to be one of the causes of the war between Venice and Genoa in 1350–1355 that dramatically affected the Byzantine Empire. The author studies terminology of various writers defining political aspirations of the Genoese Republic.